Survey of Bacterial Pathogens of Leaves and Seeds of White Mangrove (Avicennia africana) - Ukoima, H. N.; Wemedo, S. A.; Mopho, F. (Indian Forester, 2007)
Bacterial pathogens of White mangrove (Avicennia africana) were investigated in Port- Harcourt metropolis, Nigeria. Leaves and seeds samples (healthy and unhealthy) were collected and analyzed in the laboratory. Mean counts of bacteria for samples were: healthy leaves 1.04×104cfu/ml; unhealthy leaves 1.16×104cfu/ml; healthy seeds 1.15×104cfu/ml and unhealthy seeds 7.65×103cfu/ml distilled water extract. Seven bacterial genera associated with white mangrove were isolated with varying frequencies and they include Acinetobacter (4%), Alcaligenes (4%), Bacillus (20%), Corynebacterium (44%), Enterobacter (12%), Staphylococus (4%) and Streptomyces (12%). Corynebacterium species occurred in both healthy and unhealthy samples of leaves and seeds. However, counts of healthy and unhealthy leaf and seed samples are not significantly different at P>0.5.